Voluntary support in a post-welfare state: Experiences and challenges of precarity. Issue 125 (October 2021) - Power, Andrew; Hall, Edward; Kaley, Alex; Macpherson, Hannah
Highlights: Voluntary support organisations increasingly rely on non-state funding. Offers a rich account of how managers navigate a difficult funding landscape. Documents how managing care and support organisations is precarious. Concludes that relationships with local authorities are crucial for sustainability. Abstract: This paper examines voluntary sector care and support provision under a context of significantly reduced government funding. Whilst geographers have analysed the causes and aftermath of austerity on different populations, our focus is on how managers of voluntary sector organisations have had to learn and evolve through bidding for non -statutory funding to sustain their core provision. Drawing on research with voluntary support organisations in the learning disability social care sector in England and Scotland, the paper examines the effects of the state's continued reliance on the sector for core 'public' services whilst simultaneously withdrawing its funding. Using accounts from managers, the paper offers a particularly novel and potent example of voluntary sector precarity and the deepening unfinished and unsettled nature of care and support that has unfolded in the wake of austerity. Through the empirical research, attention is drawn to three levels of precarity that are experienced by those seeking to sustain voluntary support provision: voluntary sector organisation and structures, the voluntary sector workforce, and individual managers' everyday emotional and affective experiences.